2009
DOI: 10.1186/1755-7682-2-32
|View full text |Cite
|
Sign up to set email alerts
|

Third molar surgery: the patient's and the clinician's perspective

Abstract: Background: In this report, the problems of third molar surgery have been reviewed from the perspective of both patient and clinician; additionally an overall analysis of preoperative imaging investigations was carried out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1
8

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 4 publications
(7 reference statements)
1
6
1
8
Order By: Relevance
“…In our study, there was no statistically significant difference between groups when the levels of trismus at postoperative 2 and 7 days were compared. We observed that trismus was severe on day 2 in all groups and decreased on day 7, consistent with the results of other studies in the literature (17)(18)(19)(20)(21)(22). Similarly, no statistically significant difference was found between groups in edema at postoperative 2 and 7 days.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…In our study, there was no statistically significant difference between groups when the levels of trismus at postoperative 2 and 7 days were compared. We observed that trismus was severe on day 2 in all groups and decreased on day 7, consistent with the results of other studies in the literature (17)(18)(19)(20)(21)(22). Similarly, no statistically significant difference was found between groups in edema at postoperative 2 and 7 days.…”
Section: Discussionsupporting
confidence: 82%
“…Trismus reaches its maximum level 2 days after extraction and may last for 7-10 days (21). It has been claimed that the duration and severity of this complication varies from patient to patient (17)(18)(19)(20)(21). In our study, there was no statistically significant difference between groups when the levels of trismus at postoperative 2 and 7 days were compared.…”
Section: Discussioncontrasting
confidence: 37%
See 3 more Smart Citations